Pengembangan Media Interaktif Mata Kuliah Teknik Analisis Biologi Molekuler (TABM) - Fitria Lestari (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Molecular Biology Analisis Techniques (TABM) is one of the courses that discusses the basic techniques needed for molecular biology. Learning in TABM, is more emphasis on procedural, so the process by using books alone is not enough. Therefore, to support the TABM learning process, interactive were developed consisting of text, sound, images, and research videos. This type of research is R & D is a research and development design by modifying the systematics of Kemp and Dayton. The development steps are to determine the specific learning objectives of the product; prepare material and video content; creating storyboard, developing, editing, and mxing; testing and revising. The instruments used are validation sheets and questionnaires for students with qualitative and quantitative data analysis techniques. Based on the result, there are several suggestions and inputs including: design, instructions for use, product packaging, introduction of tools and initial materials, and procedures. While quantitatively it can be seen that the developed interactive media doesn’t need to be revised and is suitable for use, namely 92,1% of field experts and 70,2% of media experts. It can be concluded that the development of interactive media can be used ini procedural courses such as molecular biological analysis techniques.